Effect of Temperature on Cu2ZnSnS4 Nanomaterial Synthesized by Hydrothermal Approach - Hong, Pham Thi; Tuyen, Nguyen Viet; Thi Ha, Tran (VNU Journal of Science: Mathematics - Physics, 2018)
Cu 2 ZnSnS 4 (CZTS) is a p-type semiconductor with high absorption coefficient and direct bandgap from 1 to 1.5 eV, which is ideal for making absorber layer for solar cell. However, it is difficult to get single phase of CZTS due to the competitive formation of binary and ternary secondary phases. In this paper, we prepared CZTS nanoparticles by hydrothermal method and investigate the influence of hydrothermal temperature on the product. Raman scattering, X-ray diffraction, scanning electron microcopy, energy dispersive X-ray spectroscopy and diffusion reflective measurement were applied to characterize the products. The products are high quality nanocrystals of kesterite phase with uniform size which is applicable for solar absorber layer fabrication.